2008
DOI: 10.1007/s11842-008-9050-6
|View full text |Cite
|
Sign up to set email alerts
|

The Increasing Importance of Small-Scale Forestry: Evidence from Family Forest Ownership Patterns in the United States

Abstract: The state-level distribution of the size of family forest holdings in the contiguous United States was examined using data collected by the USDA Forest Service in 1993 and 2003. Regressions models were used to analyze the factors influencing the mean size and structural variation among states and between the two periods. Population density, percent of the population at least 65 years of age, percent of the population residing in urban areas, per capita income, income inequality, and per capita private forestla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…This affects their availability of capital to invest in and manage forest land [1,13]. A classic study in Sweden [174], and other studies in the United States, focused on the effects of tract size [241][242][243][244][245][246][247]. The most recent NIPF studies and reports continue to examine this variable [34].…”
Section: General Problems Of Promoting Management On Nipf Holdingsmentioning
confidence: 99%
See 3 more Smart Citations
“…This affects their availability of capital to invest in and manage forest land [1,13]. A classic study in Sweden [174], and other studies in the United States, focused on the effects of tract size [241][242][243][244][245][246][247]. The most recent NIPF studies and reports continue to examine this variable [34].…”
Section: General Problems Of Promoting Management On Nipf Holdingsmentioning
confidence: 99%
“…A recent study of policy tools to encourage application of sustainable timber harvesting practices in the United States and Canada also found technical assistance is the most effective way to encourage owners to apply sustainable practices, followed by cost-share programs [333]. Several recent studies stressed the importance of technical assistance to NIPF owners [334][335][336] and others looked at general aspects of incentive program effectiveness [337][338][339][340]. Two different studies found that direct contact with a forester or other natural resource professional is associated with owners being forest managers [341,342].…”
Section: Current Status Of Nipf Research On Financial Incentivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Periodic disturbance is crucial to the persistence of oak (Johnson et al, 2009), but management aimed at maintaining or restoring early-to mid-successional types may appear counterintuitive to conservation-minded small private landowners (Askins, 2001). In addition, trends in forest parcelization and land tenure in the U.S. (Best and Wayburn, 2001;Zhang et al, 2009) reduce the likelihood that landowners will embrace the long-term land management perspectives that are required for perpetuating oak (Knoot et al, 2010).…”
Section: Introductionmentioning
confidence: 99%